2023
DOI: 10.17159/sadj.v78i06.16933
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental caries among learners with disabilities attending special education schools in the eThekwini District, KwaZulu-Natal

Sinenhlanhla Gumede,
Shenuka Singh,
Mbuyiselwa Radebe

Abstract: IntroductionIndividuals with special healthcare needs may have poororal health as a result of systemic and structural issues that make it more difficult to maintain optimal oral healthstatus. As such, these individuals may require specialised, multidisciplinary oral healthcare. Furthermore, determiningthe severity of oral conditions among these people isnecessary to establish the number of people affected and the services required to improve oral healthcare for these affected populations. Aims and objectivesTo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The prevalence of caries among CWSHCN ranged from 22.5% to 85.2%. 27,28 The mean dmft/DMFT scores ranged from 0.95 (SD 2.36) to 5.51 (SD 2.1) 25,27 and 0.67 to 10.24 (SD 2.97) 25,29 for the primary and permanent dentition, respectively. The studies reported high UTNs and mostly constituted untreated caries among the study participants of between 68% 30 and 100%, 26 attributed to low restorative care.…”
Section: Oral Health Status Of Cwshcnmentioning
confidence: 99%
“…The prevalence of caries among CWSHCN ranged from 22.5% to 85.2%. 27,28 The mean dmft/DMFT scores ranged from 0.95 (SD 2.36) to 5.51 (SD 2.1) 25,27 and 0.67 to 10.24 (SD 2.97) 25,29 for the primary and permanent dentition, respectively. The studies reported high UTNs and mostly constituted untreated caries among the study participants of between 68% 30 and 100%, 26 attributed to low restorative care.…”
Section: Oral Health Status Of Cwshcnmentioning
confidence: 99%